Low Prevalence of ETV6::RUNX1 Fusion Gene in a Hispanic Population - Mata-Rocha, Minerva; Rangel-López, Angelica; Jimenez-Hernandez, Elva; Nuñez-Enríquez, Juan Carlos; Morales-Castillo, Blanca Angélica; Sánchez-Escobar, Norberto; Sepúlveda-Robles, Omar Alejandro; Bravata-Alcántara, Juan Carlos; Nájera-Cortés, Alan Steve; Pérez-Saldivar, María Luisa; Flores-Lujano, Janet; Duarte-Rodríguez, David Aldebarán; et al. (Frontiers in Pediatrics, 2022)
ETV6::RUNX1 is a genetic rearrangement of good prognosis in children with ALL. In Mexico, its prevalence is low in comparison with Caucasian populations. We developed a novel TaqMan one-step RT-qPCR approach to assess the prevalence of four genetic rearrangements in a cohort of Hispanic children with ALL from Mexico City. The prevalence of the common fusion gene transcripts was the following: TCF3::PBX1, 7.7%; BCR::ABL1p190, 3.3%; KMT2A::AFF1, 2.8%. ETV6::RUNX1 was observed in a low prevalence (10.5%) in comparison to that reported for developed countries. This is consistent with previous findings in Mexican children with ALL and similar to the reported in children from Hispanic populations. The confirmation of a low prevalence of ETV6::RUNX1 in children from a Hispanic origin represents an advance in the description of the genetic factors of ALL in these populations.